PTBPs: An immunomodulatory-related prognostic biomarker in pan-cancer - Chen, Chen; Shang, Anquan; Gao, Yuting; Huang, Jingjuan; Liu, Gege; Cho, William C.; Li, Dong (Frontiers in Molecular Biosciences, 2022)
Background The polypyrimidine tract-binding protein (PTBP) nuclear ribonucleoprotein family of proteins, including PTBP1, PTBP2 and PTBP3, regulate the process of cell proliferation, differentiation, apoptosis and carcinogenesis. PTBPs exhibit oncogenic effects in certain tumors. However, the role of PTBPs in pan-cancer remains unclear. Our study examined the clinical significance and mechanism of PTBPs in pan-cancer. Methods We compared the expression of PTBPs in paired and unpaired tissue samples from the Cancer Genome Atlas (TCGA) database. Univariate and multivariate Cox regression, Kaplan–Meier curves, and time-dependent receiver operating characteristic (ROC) curves were used to assess the prognostic significance of PTBPs in pan-cancer. The cBioPortal database also identified genomic abnormalities in PTBPs. TISIDB, TCGA, and Cellminer were used to investigate the relationship between PTBP expression and immune subtypes, immune checkpoint (ICP) genes, tumor mutational burden (TMB), microsatellite instability (MSI), tumor-infiltrating immune cells, and chemosensitivity. cBioPortal was used to search for PTBP co-expressing genes in pan-cancer, and GO and KEGG enrichment analyses were performed to search for PTBP-related signaling pathways. Results PTBPs were shown to be widely upregulated in human tumor tissues. PTBP1 showed good prognostic value in ACC, KIRP, and LGG; PTBP2 in ACC and KICH; and PTBP3 in ACC, LGG, and PAAD, with AUC > 0.7. PTBPs were differentially expressed in tumor immune subtypes and had a strong correlation with tumor-infiltrating lymphocytes (TILs) in the tumor microenvironment (TME). In addition, PTBP expressions were related to ICP, TMB, and MSI, suggesting that these three PTBPs may be potential tumor immunotherapeutic targets and predict the efficacy of immunotherapy. Enrichment analysis of co-expressed genes of PTBPs showed that they may be involved in alternative splicing, cell cycle, cellular senescence, and protein modification. Conclusions PTBPs are involved in the malignant progression of tumors. PTBP1, PTBP2 and PTBP3 may be potential biomarkers for prognosis and immunotherapy in pan-cancer and may be novel immunotherapeutic targets.